Role of MRI in Detecting Abnormal Placentation in Patients with Strong Ultrasound Concern for Myometrial Invasion - Sara Qadir Afridi, Zubair Janan Orakzai, Saadia Yasmeen, Hajra Rafique, Ayesha Kamran, Hafeez Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Abnormal placentation has raised the ratio of cesarean cases. In such obstetric complication the placenta lie at the lower segment of the uterus. These abnormal attachments of placenta to uterus and invasion to adjacent organs are the main cause of placenta previa. These are not only raising delivery challenges but also raising the mortality cases. Objective: For evaluation of the diagnostic efficacy of MRI to locate placentation abnormalities with high accuracy and sensitivity. This not only helps in preoperative delivery planning but also decreases the ratio of mortality. Study Setting: It was an observational study, conducted at radiology department of Mardan Medical Complex Mardan for the duration of six months from September 2021 to February 2022. Methods: The women suspicion of placentation abnormalities were recommended with MRI. The consecutive 185 pregnant women were included in the study. The results obtained from MRI were compared with the results obtained by C-section. Cesarean section results were considered as standard. The treatment strategy was decided in accordance with the MRI findings. The treatment strategies which opt during the CS were compared with the strategy created on the basis of MRI. Results: 115 women were diagnosed with abnormal placentation. The 70 women out of 185 were diagnosed with placenta previa. The percentage false results were seen in 18 patients. The false negative results of MRI were seen in three patients. After comparison between the findings of MRI and CS the sensitivity, positive predictive values and other parameters were calculated. The sensitivity was 97%, while the positive predictive value was 84%. The other parameters such as specificity were 79% and negative predictive value was 95%. The sensitivity, accuracy, and positive predictive values of the planning strategy created for treatment on the basis of MRI findings were calculated. There was significant correlation between the findings of MRI and CS. Conclusion: For the future planning of treatment strategy for the women suspected of abnormal placentation, MRI is highly suggested diagnostic tool with better efficacy and sensitivity. This imaging modality helps in proper and accurate diagnosis of abnormal placentation. Keywords: Abnormal placentation, obstetric complications, treatment strategy, placenta previa.